Judgment, Nonsense and the Unity of the Proposition: Revisiting Wittgenstein's Criticism of Russell - Segatto, Antonio [UNESP] (Krk Ediciones, 2021)
This paper has two aims. First, it aims to show that most commentators misunderstand Wittgenstein's criticism of Russell's theory of judgment in that they share a common assumption, namely: when interpreting the so-called nonsense objection, they mistakenly attribute to Wittgenstein a substantial conception of nonsense that is alien to his austere conception of nonsense. Second, it aims to suggest that this criticism should be seen as part of Wittgenstein's overall criticism of Russell's approach to the problem of the unity of the proposition.
Keywords: Judgment; Nonsense; Unity of the Proposition; Revolt against Idealism